PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN GENERASI MILENIAL DI ERA DIGITAL - Tari Nur Syafni Sinaga; Zairnati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This research analyzes the impact of job satisfaction on the performance of millennial generation employees in the digital era. In this case, job satisfaction is considered a crucial element that can improve performance, especially in a work environment influenced by technology. The findings show that job satisfaction has a significant positive influence on employee performance, with a contribution reaching 91.5% in increasing productivity. This research emphasizes the importance of understanding the characteristics of the millennial generation to create a work environment that supports and maximizes their performance.